Evidence for Circulation of Bovine Viral Diarrhoea Virus Type 2c in Ruminants in Southern Italy. Issue 6 (23rd November 2016) - Decaro, N.; Lucente, M. S.; Lanave, G.; Gargano, P.; Larocca, V.; Losurdo, M.; Ciambrone, L.; Marino, P. A.; Parisi, A.; Casalinuovo, F.; Buonavoglia, C.; Elia, G.
Summary: Recently, bovine viral diarrhoea virus type 2c (BVDV‐2c) was responsible for a severe outbreak in cattle in northern Europe. Here, we present the results of an epidemiological survey for pestiviruses in ruminants in southern Italy. Pooled serum samples were obtained from 997 bovine, 800 ovine, 431 caprine and eight bubaline farms, and pestiviral RNA was detected by molecular methods in 44 farms consisting of 16 cattle and one buffalo herds and of 21 sheep and six goat flocks. Twenty‐nine and 15 farms were infected by BVDV‐1 and BVDV‐2 strains, respectively. BVDV‐1 strains were recovered mainly from cattle and were heterogeneous, belonging to the subtypes 1b, 1u, 1e, 1g and 1h. In contrast, all BVDV‐2 viruses but two were detected in sheep or goats and were characterized as BVDV‐2c by sequence analysis of 5′UTR. These strains displayed high genetic identity to BVDV‐2c circulating in cattle in northern Europe and were more distantly related to a BVDV‐2c isolate recovered from a cattle herd in southern Italy more than 10 years before. The circulation of a BVDV‐2c in small ruminants suggests the need for a continuous surveillance for the emergence of pestivirus‐induced clinical signs in southern Italian farms.